The Role of Surface Hydrophobicity on the Structure and Dynamics of CO2 and CH4 Confined in Silica Nanopores - Mohammed, Sohaib; Sunkara, Ajay Krishna; Walike, Casey Elizabeth; Gadikota, Greeshma (Frontiers in Climate, 2021)
Advancing a portfolio of technologies that range from the storage of excess renewable natural gas for distributed use to the capture and storage of CO2 in geological formation is essential for meeting our energy needs while responding to challenges associated with climate change. Delineating the surface interactions and the organization of these gases in nanoporous environments is a less explored but highly relevant approach to develop novel materials for gas storage or for predicting the fate of stored gases in subsurface environments. To this end, the molecular scale interactions underlying the organization and transport behavior of CO2 and CH4 molecules in silica nanopores need to be investigated. To probe the influence of hydrophobic surfaces, a series of classical molecular dynamics (MD) simulations are performed to investigate the structure and dynamics of CO2 and CH4 confined in OH-terminated and CH3-terminated silica pores with diameters of 2, 4, 6, 8, and 10 nm at 298 K and 10 MPa. Higher adsorption extents of CO2 compared to CH4 are noted on OH-terminated and CH3-terminated pores. The adsorbed extents increase with the pore diameter. Further, the interfacial CO2 and CH4 molecules reside closer to the surface of OH-terminated pores compared to on the surface of CH3-terminated pores. The lower adsorption extents of CH4 on OH-terminated and CH3-terminated pores result in higher diffusion coefficients compared to CO2 molecules. The diffusivities of both gases in OH-terminated and CH3-terminated pores increase systematically with the pore diameter. The higher adsorption extents of CO2 on OH-terminated and CH3-terminated pores are driven by the higher van der Waals and electrostatic interactions with the pore surfaces while CH4 adsorption is mainly due to van der Waals interactions with the pore walls. These findings provide the interfacial chemical basis underlying the organization and transport behavior of pressurized CO2 and CH4 gases in confinement.